Genealogy of Islamic Business Organization: The Institutional Approach Towards Current Islamic Corporate Law - Afdal, Windi; Murwadji, Tarsisius; Supriyatni, Renny; Mulyati, Etty; Mbilinyi, Francis Daniel (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2024)
This article examines the social foundation which posed challenges to the adoption of corporate form as a business entity within the framework of Islamic legal tradition. This article employs juridical-normative research analysis with socio-legal approach. This paper concludes: (1) The corporate legal form was not required by the medieval Islamic legal system as well as the case in Western Europe due to several reason such as: an institutional vacuity; withdrawal of community capital resources into waqf institutions; stagnancy in institutional development of business organizations in Islamic law; and inability of the Muslim business elite to consolidate power. (2) In classical fiqh discussions, Islamic business organizations do not have legal personality. The closest approximation to corporate legal entities found in Islam have been bayt al-māl (public treasury), mosque property, and waqf (trusts). Recently, the scholars have approved the corporate form on the basis of fiqh principles of qiyas (analogy) and istihsan, or masaliha mursalah (public interest).